Influence of body mobility on attention networks in school-aged prematurely born children: A controlled trial - Rosenbaum, Joëlle; Ceyte, Hadrien; Hamon, Isabelle; Deforge, Hélène; Hascoët, Alexandre M. J.; Caudron, Sébastien; Hascoët, Jean-Michel (Frontiers in Pediatrics, 2022)
School-aged prematurely born children (PC) have a higher risk of academic difficulties, which may be partly explained by attention difficulties. It has been suggested that children’s attentional performance might be influenced by their body posture and spontaneous body motion. The aim of this study (ClinicalTrials.gov – NCT 03125447) was to test the influence of three body mobility conditions on the three functions of attention (alertness, orienting, and executive control) among school-aged PC vs. term-born children (TC). Notably, 21 PC and 21 TC performed the Attention Network Test for Children in three body mobility conditions, namely, sitting and standing imposed fixed postures and a free-to-move condition. The children’s median reaction times were compared between trials (1) with and without alerting cues, (2) with valid and invalid orienting cues, and (3) with and without distracting information, to calculate the performance of alertness, orienting, and executive control, respectively. Results showed that with distracting information, PC exhibited significantly slower responses in the standing-still posture than in the sitting-still posture (1,077 ± 240 vs. 1,175 ± 273 ms, p < 0.05), but not TC. No difference was observed with the free-to-move condition. PC and TC did not significantly differ in alertness or orienting, regardless of body mobility condition. These data suggest that PC must use executive resources to stand still and maintain position, which impairs their performance during executive tasks. We speculate that these results may be related to less developed postural control and motor inhibition in PC.